Green HRM and Environmental Performance in Hospitality Sector: The Roles of Employee Innovation and Environmental Regulation - Yanuar Surya Putra; Ambar Istiyani (Research Synergy Foundation, 2026)
Human resources are crucial to an organization's environmental success. Green HRM practices and green innovative work behavior provide a foundation for enterprises to manage their environmental performance effectively. This study aims to promote environmentally conscious green HRM and innovative work behavior to enhance the environmental performance of hospitality sector firms in Salatiga through the role of environmental regulation as a moderator. The number of samples is 271 employees in the hospitality sector. Additionally, data collection was conducted via a survey, and the analysis tool used was partial least squares-based mediating and moderating structural equation modeling. The result showed that in the hospitality sector, Green Innovative Work Behavior (GIWB) acts as a crucial mediator between Green Human Resources Management (GHRM) and environmental performance. Furthermore, environmental regulation moderates the relationship between Green Human Resources Management (GHRM), Green Innovative Work Behavior (GIWB), and environmental performance in the hospitality sector. When environmental regulations are stringent, they strengthen the impact of GHRM on GIWB, leading to enhanced environmental performance. Enhancing GHRM practices to foster GIWB can be crucial for achieving compliance and excelling in environmental performance. Even in less regulated environments, organizations can use GHRM to foster a culture of innovation that anticipates future regulatory changes, ensuring they remain ahead of the curve in environmental sustainability.